Motor skills of primary school children: The differences compared to age - Pavlović Slobodan Lj; Marinković Dragan B.; Mitrović Nebojša Z. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
Physical education, from the earliest age in preschool institutions, and then through primary and secondary schools, is the only place where children can, in the right way, acquire the knowledge on sports, skills, behaviour, necessary in order to get the continuity of physical activities in the adulthood. Primary school is a period when the students experience great changes in the overall developing status. Therefore, Physical Education has a fundamental role in the development of psychosomatic characteristics of children. While planning lessons of Physical Education, there is a special emphasis on the development of motor skills. The goal of this research refers to the establishing of the existing differences in the motor space of primary school children in relation to age. The sample consisted of 231 examinees who attended 3rd, 4th, 5th and 6th grade (age 11 ± 1.6 years), out of which there were (N = 109; TV = 147.6 ± 7; TM = 39.6 ± 7.1) boys, and (N = 122; TV = 148.3 ± 5.9; TM = 40 ± 5.3) girls. All examinees were the students from the territory of Zlatibor region and with the signed permission for performing testing by both parents. Motor skills have been estimated within school Physical Education, all with the purpose of getting more realistic picture on the motor skills of children. The presented results point to the existing differences between the groups of examinees of both genders on a general level, as well as the individual differences within the motor space. These differences are more noticeable with boys (F = 5.92; P = .00) than with girls (F = 4.79; P = .00). Statistically greater differences with boys have been noted in the following variables: "Hand tapping", "Hand clapping", "Throwing basketball ball", "the 30 m running flying start", "Pull-ups", and "Torso lift-ups". With girls, statistically significant difference have been notes in the following variables: "Throwing basketball ball", "the 30 m running flying start" and "Torso lift-ups". The value of this work is reflected in the fact that, during testing, a great number of tests were used for estimation of the examinees' motor space, all with the purpose of getting more complete picture on the existence of differences among the groups, categorised by gender and age. The importance of testing and perception of differences in motor skills and their monitoring presents one of the important activities during PE classes, all with the purpose of the adequate lesson programming, but also monitoring the motor development.